2010
DOI: 10.1111/j.1467-8608.2010.01601.x
|View full text |Cite
|
Sign up to set email alerts
|

Stock picking, market timing and style differences between socially responsible and conventional pension funds: evidence from the United Kingdom

Abstract: As far as we are aware, this study presents the first comparative analysis of the stock picking and market timing abilities of managers of conventional and socially responsible (SR) pension funds, and of their use of superior information. For the United Kingdom, the results obtained show a slight stock picking ability on the part of SR pension fund managers (although it disappears if multifactorial models are considered), and a negative market timing ability on the part of both SR and conventional pension fund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 26 publications
2
22
1
Order By: Relevance
“…In terms of selectivity, the results show that the significantly lower abilities of SRI funds, in comparison to their matched-peers, are attributed to funds that use negative screens, as well as the superior ability of SRI funds to time the market and local factors. A possible explanation for this result is the fact that SRI fund 21 Evidence of "perverse" market timing abilities is also found by many previous studies on conventional funds (e.g., Ferson & Schadt, 1996;Sawicki & Ong, 2000) and by most of the existing studies on SRI mutual funds (e.g., Ferruz, Muñoz, & Vargas, 2010;Gregory & Whittaker, 2007;Kreander et al, 2005;Muñoz et al, 2014;Renneboog et al, 2008). 22 Muñoz et al (2015) also find evidence that both SRI and conventional fund managers in the US successfully time the book-to-market factor.…”
Section: Managerial Abilities In Crisis and Non-crisis Periodssupporting
confidence: 59%
“…In terms of selectivity, the results show that the significantly lower abilities of SRI funds, in comparison to their matched-peers, are attributed to funds that use negative screens, as well as the superior ability of SRI funds to time the market and local factors. A possible explanation for this result is the fact that SRI fund 21 Evidence of "perverse" market timing abilities is also found by many previous studies on conventional funds (e.g., Ferson & Schadt, 1996;Sawicki & Ong, 2000) and by most of the existing studies on SRI mutual funds (e.g., Ferruz, Muñoz, & Vargas, 2010;Gregory & Whittaker, 2007;Kreander et al, 2005;Muñoz et al, 2014;Renneboog et al, 2008). 22 Muñoz et al (2015) also find evidence that both SRI and conventional fund managers in the US successfully time the book-to-market factor.…”
Section: Managerial Abilities In Crisis and Non-crisis Periodssupporting
confidence: 59%
“…To the best of our knowledge, there are only two papers that focus on this subject, one for the US (Girard et al, 2007) and another for the UK market (Ferruz et al, 2010), and they exhibit contradictory results. While the former found that most SRI funds exhibit neutral market timing and significantly negative selectivity skills, the latter showed that both SRI and conventional pension fund managers exhibit neutral stock-picking and significantly negative market timing abilities.…”
Section: Introductionmentioning
confidence: 93%
“…The market exposure (β 1 ) is similar in both conventional and SR pension funds. With regard to the style strategies, conventional and SR funds invest in small cap and growth values, in line with Ferruz et al (2010). Nonetheless, the momentum strategies are diverse: absent or positive momentum strategies in conventional funds (panel A), and contrarian momentum strategies in SR funds (panel B).…”
Section: Style Timing Abilitiesmentioning
confidence: 93%
“…To date, only Ferruz et al (2010) provide a comparative analysis of stock-picking and market timing abilities in pension funds. Accordingly, this analysis extends the existing literature on SR pension funds, with the results showing significantly negative performance and similar investment strategies in both conventional and SR pension funds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation